The use of discrete event simulation and dBase IV to develop a decision support tool for production planning - Pauw, J. C. H.(Jacobus Cornelis Holtz) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1990.